Efficacy and Safety of Esmolol in Neonatal Cardiac Surgery with Cardiopulmonary Bypass (CPB) for d-Transposition of the Great Arteries (d-TGA) - Blank, Anna-Eva; Zajonz, Thomas; Gruschwitz, Inga; Neuhäuser, Christoph; Akintürk, Hakan; Jux, Christian; Backhoff, David; Justus Liebig University Giessen (My University, 2024)
Objective: D-Transposition of the great arteries (d-TGA) is the most common congenital heart disease requiring surgical correction within the neonatal period. Sinus tachycardia often persists postoperatively, potentially affecting cardiac function. This study aimed to investigate the efficacy and safety of the short-acting beta-1-selective beta-blocker esmolol in controlling heart rate in neonatal cardiac surgery with cardiopulmonary bypass (CPB). Methods: A retrospective cohort study was conducted on neonates undergoing surgery for d-TGA. The study cohort included 112 patients, divided into an esmolol intervention group (n = 57) and a control group (n = 55). Baseline characteristics, hemodynamic parameters and outcome measures were assessed. Results: In the esmolol group, median heart rate at ICU admission was significantly higher compared to the control group (155 vs. 147 bpm, p = 0.018). After a median time of 11 h, heart rate was lower among the esmolol patients (135 vs. 144 bpm, p < 0.001). There were no differences in other hemodynamic parameters between the two groups. Patients treated with esmolol required longer catecholamine support while no difference regarding survival, duration of invasive ventilation and ICU stay were noticed. Conclusion: No relevant hemodynamic difference was seen between neonates treated with perioperative esmolol and the control group and outcome did not differ. This indicates non-inferiority of perioperative betablocker therapy in young age. Prospective and placebo-controlled assessment of perioperative esmolol therapy in neonates is needed.
Keywords: ddc:610